New catalysts for hydrogen production from H2S: Preliminary results - Guldal, N. O.; Figen, H. E.; Baykara, S. Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Hydrogen sulfide (H2S), a toxic and corrosive industrial byproduct, is available in vast amounts. It is also found in varying concentrations in fossil fuel reserves and natural waters. Sulfur is generally recovered from its treatment in Claus Plants, where its hydrogen content is converted into water. Hydrogen, a substantial feedstock and a sustainable fuel, can also be recovered from H2S if convenient methods can be developed. In the present study perovsldte catalysts that are being developed for hydrogen production via thermal decomposition of H2S are introduced, and some preliminary results pertaining to their structural properties and performance are presented. The aim of the study is catalytic decomposition of H2S, a liability, by converting it into hydrogen and sulfur, products with economic value. Copyright (c) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Hydrogen sulfide; Catalyst; Perovskite; Metal oxide; THERMAL-DECOMPOSITION; SULFIDE; SULFUR; MECHANISM; KINETICS; VANADIUM; THERMOLYSIS; SEPARATION; PYROLYSIS; METHANE; Chemistry; Electrochemistry; Energy & Fuels